Impact of black point incited by Alternaria alternata on wheat trade, seed quality and seed germination - V.A. SOLANKI, MAHENDRA PARTAP*and (Indian Phytopathology, 2016)
The impact of black point on average price reduction of wheat Rs. 10.16 was observed in black point infected seed lots in comparison with healthy seed lots. Price of wheat decreased with an increase of black point incidence in seed lots. The impact on seed quality showed the seed hardness index significantly higher in healthy seeds (82.0) than black point infected seeds (76.8). Whereas, quality characters, single kernel weight, seed diameter and 1000 grain weight were 15.49, 6.89 and 13.37 per cent higher in black point infected seeds than healthy seeds, respectively. The effect of black point infection on seed germination under field conditions revealed the non significant difference in germination between healthy seeds and black point infected seeds. Vigour index was comparatively higher in healthy seeds than black point infected seeds.